Spectral specific standardized low-resolution brain electromagnetic tomography default mode connectivity network and plasticity alterations in left vertebral artery stent patients. (March 2020) - Lv, Yan; He, Xiangying; Zhao, Eryi; Deng, Yidong; Huang, Yingliu; Chen, AC; Huang, Shixiong; Qin, Qi; Liu, Tao; Wen, Guoqiang
Objective: Vertebral stenting is a valid treatment for posterior stroke. However, the outcome and prognostic factors in the Asian population of vertebral stent are not clear. This study was performed to investigate the quick effect and plasticity alterations of left vertebral artery stenting treatment and to explore the underlying electroencephalogram biomarkers for the prognosis. Method: Electroencephalogram default mode network activity, serum brain-derived neurotrophic factor, and basic neuropsychology estimations were obtained from nine male left vertebral artery stenosis patients who underwent left vertebral artery stenting 24 h before and after left vertebral artery stenting therapy. Result: The beta-1 (13–24 Hz) electroencephalogram field power of the pre–left vertebral artery stenting group was significantly higher compared to that of the post–left vertebral artery stenting and control group ( p  < 0.05). The significant different standardized low-resolution brain electromagnetic tomography brain areas of beta-1 band Brodmann areas are 17R, 17L, 18R, 18L, 22R, 22L, 37R, and 37L. The nonliner lag ratio–based functional connectivity analysis showed global increase of connectivity in beta-1 standardized low resolution brain electromagnetic tomography network. Serum brain-derived neurotrophic factor did not show statistically significant changes during groups. Conclusion: Electroencephalogram default mode network provided a functional aspect of left vertebral artery stenting patients, and the beta-1 band power and distribution alterations could be candidate measurements for the plasticity alterations and prognosis evaluation.